The Influence Of Sharia Compliance, Bank Size And Complexity On Fraud In Sharaia Banks - Efri Syamsul Bahri; Hasna’ Nadiyah Hasanah; Ai Nur Bayinah (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2022)
This research aimed to analyse the influence of Sharia compliance, size, and complexities on fraud in Sharia Banking. The method applied in this study was quantitatively associated. The research design is based on an associative quantitative approach. Data were collected during the Sharia banking period from to 2015-2019. The data analysis was completed using a panel information regression approach and processed using the Eviews 9 application. In this study, the compliance rate of Sharia banks was measured using the profit-sharing ratio (PSR), Islamic investment ratio (IIR), and Islamic income ratio (IsIR). Size is measured using the logarithm of natural (Ln) total assets and complexities are measured using the square root of the number of offices inside Sharia banks. The object of this analysis is Sharia banking in Indonesia. Sampling was performed using a specific purposive sampling procedure to obtain data from nine Syariah Banking from to 2015-2019. The results of this study indicate that Sharia compliance (PSR, IIR, and IsIR), size, and complexity simultaneously have a significant effect on fraud in Sharia banks with probability levels of 0.0002 and 0.0237. In part, size and complexity have significantly positive effects on fraud. Sharia banks have probability levels of 0.1056, 0.7866, and 0.3817 for compliance (PSR, IIR, and IsIR, respectively).